Observations on Some Climatic Variables and Dietary Influence on the Performance of Cultivated African Giant Land Snail (Archachatina marginata): Notes and Records - Ejidike, B.N.; Afolayan, T.A.; Alokan, J.A. (Pakistan Journal of Nutrition, 2004)
NOT AVAILABLE